P034: Computed tomography rates for emergency department super-users. (May 2020) - Savage, D.; North, R.; McKay, G.; McMillan, C.; Stonebridge, R.; Piper, B.; Jeffery, A.; Ohle, R.; VanderBurgh, D.
Abstract : Introduction: Most emergency departments (ED) in Canada have a population of high frequency users that present to the ED on a regular basis. These patients are well described in the literature and typically defined by a frequency of 8-10 visits/year. In Thunder Bay, Ontario we have a significant population of patients that present more often that we have termed "super-users". These patients often are typically from a vulnerable population with multiple co-morbidities and a high mortality rate. Although their risk for poor health outcomes is well recognized, both the chronicity and complexity of their symptoms often contributes to diagnostic dilemmas. The decision to order a computed tomography (CT) scan can be a difficult balance between ruling out life threatening diagnoses and exposing the patient to excessive radiation. Our objective was to describe how often these super-users of the ED received a CT scan and what types of imaging were completed. Methods: The Thunder Bay Regional Health Sciences Centre is a geographically isolated hospital in Northwestern Ontario with the next closest hospital based CT scanner greater than 300 km away. Based on previous literature and our preliminary scoping of the super-user group, we have identified a minimum of 25 visits as the threshold. A retrospective chart review was conducted for the year 2017 using our electronic medical record. Patient demographic data was collected along with the type and number of CT scans into a standardized collection tool. Results: Our preliminary results showed that our total population of super-users was 75 patients with an average of 32 visits to the ED per year. A total of 76% of the patients had a CT scan completed at least once. On average these patients have a CT during 10% of their visits with head CT comprising 50% of the imaging and abdominal/pelvis imaging comprising another 45%. For 20% of these super-users, they had CTs on 20% of their visits. From this population, only 10% of the patients had surgery in 2017 while 7% of visits required admission to hospital. The most common diagnoses for these patient visits relate to mental health/addictions, gastrointestinal complaints and infection. Conclusion: This study has shown that a significant number of our super-user population are receiving multiple CTs. Our next step is collect data on individual radiation doses and calculate exposure risks. We hope to inform policy and decision-makers who are developing programs to treat the underlying cause of their high resource use.